Field assessment of a Cold-In place-recycled pavement: Influence on rolling noise. (1st October 2018) - Vázquez, V.F.; Terán, F.; Huertas, P.; Paje, S.E.
Abstract: This work aims to study some surface characteristics (tire/pavement noise, texture, roughness and dynamic stiffness) of an experimental test track section fabricated with Cold-In place-Recycled (CIR) pavement. The field assessment of the experimental section was carried out after two months curing, and prior to being overlaid with a hot bituminous mixture. CIR pavement may be a good paving solution in some cases. These mixtures present some characteristics that make them environmentally friendly mixes regarding conventional hot bituminous mixtures, such as their lower temperature of fabrication (low greenhouse gas emissions and fuel consumption) and the use of recycled materials from the same pavement to be rehabilitated. According to the research results, CIR pavement could be presented as a reduced noise surface regarding other conventional hot bituminous mixtures. Dynamic stiffness and macrotexture of this studied section mitigate noise at medium frequencies of the tire/pavement noise spectrum, which are the main frequencies of the overall tire/pavement noise levels. Tire/pavement noise generation mechanisms in CIR pavements are discussed according to the achieved results. Graphical abstract: Highlights: Acoustic and texture characteristics of Cold-In place-Recycled pavement are assessed. Cold-In place-Recycled mixes may reduce noise regarding some conventional mixes. Dynamic stiffness and macrotexture play a key role in tire/pavement noise reduction. MPD may be linked to noise attenuation at high frequencies.